Independent and joint exposure to passive smoking and cooking oil fumes on oral cancer in Chinese women: a hospital-based case-control study. (2nd October 2016) - He, Baochang; Chen, Fa; Yan, Lingjun; Huang, Jiangfeng; Liu, Fangping; Qiu, Yu; Lin, Lisong; Zhang, Zuofeng; Cai, Lin
Abstract: Conclusions: Passive smoking and COF exposure are independent risk factors for oral cancer in Chinese women, with the multiplicative interactions from combined exposures. Avoiding exposure to environmental tobacco smoke and COF may contribute to the prevention of oral cancer in Chinese women. Objective: To evaluate the independent and joint effects of passive smoking and cooking oil fumes (COF) on oral cancer in Chinese women. Methods: A case-control study was performed including 238 female patients with pathologically confirmed oral cancer and 470 controls as age-matched controls. Face-to-face interviews were conducted based on a structured questionnaire. The effects of passive smoking and COF exposure were analyzed using non-conditional logistic regression models. Results: Passive smoking significantly increased the risk of oral cancer in Chinese women: adjusted ORs were 2.12 (95% CI = 1.11–4.07) for those only exposed before age 18, 1.52 (95% CI = 1.01–2.31) for those only exposed after age 18, and 2.38 (95% CI = 1.47–3.85) for those both exposed before and after age 18. In addition, COF exposure was significantly associated with a risk of oral cancer (adjusted ORs were 1.69 (95% CI = 1.03–2.78) for light exposure and 2.06 (95% CI = 1.21–3.50) for heavy exposure). Furthermore, there was a significantly multiplicative interaction between passive smoking and COF for oral cancer.